A distributed-parameters transmission line model developed directly in the phase domain - Souza Jr., Newton V. [UNESP]; Carvalho, Carolina G. [UNESP]; Kurokawa, Sérgio [UNESP]; Pissolato, José (Taylor & Francis, 2013)
This article shows a transmission line model developed directly in the phase domain. The proposed model is based on the relationships between the phase currents and voltages at both the sending and receiving ends of a single-phase line. These relationships, established using an ABCD matrix, were extended to multi-phase lines. The proposed model was validated by using it to represent a transmission line during short-and open-circuit tests. The results obtained with the proposed model were compared with results obtained with a classical model based on modal decomposition. These comparisons show that proposed model was correctly developed. © 2013 Taylor and Francis Group, LLC.
Keywords: ABCD matrix; frequency dependence; modal decomposition; phase domain; transmission line model; Frequency dependence; Modal decomposition; Phase domain; Transmission line models; Electromagnetic wave emission; Transmission line theory